Анализ вибровозмущающих сил в асинхронных двигателях при обрыве сегментов короткозамыкающих колец обмотки ротора на основе цепе-полевой математической модели - Васьковский, Ю.Н.; Гераскин, А.А.; Коваленко, М.А. (Електротехніка і електромеханіка, 2011)
A circuit-field mathematical model is developed to analyze electromagnetic vibration-exciting forces and signals of vibration sensors in squirrel-cage induction motors under damage of short-circuited rotor ring segments. Results of spectrum analysis are applied to reveal a set of diagnostic indicatiors which allow identifying this type of damage.